Scientific Sources and Teaching Contexts Throughout History: Problems and Perspectives - Bernard, Alain (Springer Netherlands Imprint: Springer, 2014)
Making clear the meaning of "context" and highlighting the complexity hidden in the words "teaching" and "learning", this book presents comparatist approaches and emphasizes the notion of teaching as projects embedded in coherent treatises or productions
Description based upon print version of record
Keywords: Aufsatzsammlung; Geschichte; Wissenschaftsphilosophie; Wissenschaft; Wissenschaftslehre